NILAI-NILAI ESTETIS TARI GAMBYONG - Sri Rochana Widyastutiningrum (Institut Seni Indonesia Surakarta, 2002)
The performance of Gambyong Dance has a relationship with aesthetic value. This dance expresses the feminineness, softness, and liveliness of a woman. The aesthetic values of Gambyong Dance especially of the harmony between the movement of the dancer and the rhythm of the melody of the drumming. To present the dance, the choreographer and the emotion of the dancer have a great influence in determining the aesthetic of Gambyong Dance. So, if the dancer have a good emotion and is able to express It perfectly, the aesthetic values will exist and might become the expression of the erotic and sensual Gambyong Dance. This expression will fulfill if the Gambyong Dance danced by the dancer who meet the criteria of Jogèd Mataram and Hastha Sawanda dances.Key word: Aesthetic value, Joged Mataram, and Hastha Sawanda.